Transcriptome analysis reveals mRNAs and long non-coding RNAs associated with fecundity in the hypothalamus of high-and low-fecundity goat - Hou, Biwei; Mao, Min; Dong, Shucan; Deng, Ming; Sun, Baoli; Guo, Yongqing; Li, Yaokun; Liu, Dewu; Liu, Guangbin (Frontiers in Veterinary Science, 2023)
As an important organ that coordinates the neuroendocrine system, the hypothalamus synthesizes and secretes reproductive hormones that act on the goat organism, thereby precisely regulating follicular development and reproductive processes in goats. However, it is still elusive to explore the mechanism of hypothalamic effects on goat fertility alone. While long-stranded non-coding RNA (LncRNA), an important regulator of the hypothalamus associated with goat fertility, plays a role in follicular development in goats, its expression pattern and potential function in the hypothalamus are still unclear. Therefore, RNA-seq was used to analyze the gene expression in hypothalamic tissues of goats in high fertility group (HFG: litter size per litter ≥2) and low fertility group (LFG: litter size per litter =1), and identified the differential lncRNAs and mRNAs and their associated pathways related to their fertility. The results showed that a total of 23 lncRNAs and 57 mRNAs were differentially expressed in the hypothalamic tissue of high and low fertility goats. GO terms and KEGG functional annotation suggest that DE lncRNAs and DE mRNAs were significantly enriched in hormone-related pathways regulating ovarian development, hormone synthesis and secretion, regulation of reproductive processes, Estrogen signaling pathway, Oxytocin signaling pathway and GnRH signaling pathway, as well as in regulation of sister chromatid cohesion and Starch and sucrose metabolism. And we constructed a co-expression network of lncRNAs and target genes, and identified reproduction-related genes such as NMUR2, FEZF1 and WT1. The sequencing results of the hypothalamic transcriptome have broadened our understanding of lncRNA and mRNA in goat hypothalamic tissue and provided some new insights into the molecular mechanisms of follicle development and regulation of its fertility in goats.